2015
DOI: 10.1039/c5gc00777a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient reduction of bromate to bromide over mono and bimetallic ZSM5 catalysts

Abstract: The reduction of bromate to bromide was successfully catalyzed by mono and bimetallic catalysts based on ZSM5 zeolites. This reaction is important since the presence of bromate in water is potentially carcinogenic to humans. The catalysts were prepared by ion-exchange and incipient wetness methods with different metals (copper, palladium, rhodium and thorium) using ZSM5. Several analytical techniques (N 2 adsorption, TPR experiments, NH 3 -TPD, FTIR, XRD, SEM/EDX and TEM/EDX) were used to characterize the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Thus, SP60 sample demonstrated the best performance among them. Table 2 compares the catalytic bromate reduction activity between SP60 sample and various Pd-based catalysts reported in literature 34 35 36 40 41 42 43 44 45 46 , and their initial bromate reduction rate was calculated based on the amount of active Pd component. It demonstrated clearly that our SP60 sample had a superior bromate reduction performance among these Pd-based catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SP60 sample demonstrated the best performance among them. Table 2 compares the catalytic bromate reduction activity between SP60 sample and various Pd-based catalysts reported in literature 34 35 36 40 41 42 43 44 45 46 , and their initial bromate reduction rate was calculated based on the amount of active Pd component. It demonstrated clearly that our SP60 sample had a superior bromate reduction performance among these Pd-based catalysts.…”
Section: Resultsmentioning
confidence: 99%
“… 34 reported the first catalytic reduction of bromate with noble metal catalysts loaded on various powder supports. Since then, efforts had been made to develop various catalysts for the catalytic reduction of aqueous bromate with encouraging results 35 36 37 38 39 . However, these catalysts could not be efficiently separated from treated water due to their powder form supports, and their dispersion into the aqueous environment may result in secondary pollution and a high cost due to their active components of expensive noble metals.…”
mentioning
confidence: 99%
“…Recently, photocatalysts using zeolites have also attracted great interest [19][20][21][22][23][24][25]. These microporous structures are currently used as catalysts, adsorbents and biomaterials [26][27][28]. Zeolites are crystalline aluminosilicate materials containing SiO 4 and AlO 4 tetrahedrons (elementary building units), which are linked at their corners through a shared oxygen atom, and this results in an inorganic macromolecule with a structurally different threedimensional framework [29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent screening studies by the Pereira and Neves team [34][35][36][37][38], several hydrogenation metals were evaluated for BrO 3 − and NO 3 − reduction, and Pd-based catalysts were still reported as having the highest activity. However, our group recently found that a Rh/C catalyst exhibited substantially higher activity than Pd/C for ClO 3 − reduction in acidic solution [39].…”
mentioning
confidence: 99%